Thomas Jefferson and Education - Heslep, Robert D. (New York Random House, 1969)
Thomas Jefferson and Education. Thomas Jefferson was regarded as a significant figure in numerous areas of though and action. He was esteemed for his talent and accomplishments in such fields as natural science, education, agriculture, architecture, and technology as well as politics.
Keywords: Education